Handbook of Arabian medicinal plants - Ghazanfar, Shahina A. (CRC Press, 1994)
"The Handbook of Arabian Medicinal Plants is the first illustrated reference on the uses of plants in the Arabian Peninsula. It documents and preserves the existing knowledge in a region where social patterns are rapidly changing. The book emphasizes the need for preserving social and cultural patterns and examines the close relationship between those patterns and nature. This excellent source identifies more than 250 species of plants and describes their medicinal uses. Biochemical information and references are also included for each species."--Provided by publisher.